Harmonizing the past: EEG-based brain network unveil modality-specific mechanisms of nostalgia - Shuxiang, Hu; Ying, Liu; Qizong, Yue; Huan, Zhao; Maoping, Zheng (Frontiers in Psychology, 2025)
IntroductionNostalgia is a complex emotional experience involving fond memories of the past and mild sadness, characterized by positive emotions associated with reflecting on previous events. It can awaken emotional memories of loved ones or significant events, contributing to an increase in positive emotions. An unresolved question regarding nostalgia is whether different channels of nostalgia input exhibit distinct mechanisms.MethodsThis study examined the emotional and neural effects of nostalgia using various sensory channels through behavioral experiments and electroencephalography (EEG) measurements conducted with college students in China. Participants' emotions were elicited using nostalgic and non-nostalgic stimuli presented through three different sensory channels: auditory (sound only), visual (e.g., still images or synchronized lyrics related to music), and audiovisual (a combination of sound and visual elements, such as music videos).ResultsThe results demonstrated that nostalgic stimuli elicited significantly higher levels of emotional arousal, pleasure, nostalgia, and dominance compared to non-nostalgic stimuli. At the neural level, nostalgic stimuli enhanced the connection strength, global and local efficiency, and diminished eigenpath length of brain networks in the alpha and gamma bands. Additionally, nostalgia through the auditory channel induced higher activity intensity in the theta and gamma bands and increased brainwave amplitudes in the alpha bands. The audiovisual channel was capable of triggering stronger alpha-wave responses than the visual channel alone.DiscussionThese findings suggest that nostalgia effectively triggers positive emotional states and enhances cognitive processing. The audiovisual channel, in particular, showed advantages in eliciting alpha-wave responses. Further research is needed to explore the potential of nostalgia as an adjunctive therapeutic tool.